Al-Hadits dalam Pandangan Orientalis (Joseph Schacht) - Ucin Muksin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
Since early period of Islam, opinion about hesitant to position of hadits be seen. That is ever occurs at classic period of hadits studies, but stopped with coming Imam Syafi’i. In modern era, the hesitant attitude back occurred by Joseph Schacht, an orientalist. He see a fact about conspiration of specialist of law in Islamic history. With it’s projecting back theory, he investigate un-valid practices by specialist both law and hadits.Since early period of Islam, opinion about hesitant to position of hadits be seen. That is ever occurs at classic period of hadits studies, but stopped with coming Imam Syafi’i. In modern era, the hesitant attitude back occurred by Joseph Schacht, an orientalist. He see a fact about conspiration of specialist of law in Islamic history. With it’s projecting back theory, he investigate un-valid practices by specialist both law and hadits.